The Application of Greedy Algorithm in OLTC Tap Setting for Voltage Stability of a 60 MVA Power Transformer - Ahmad Azhari Batubara; Misbahul Jannah; Muhammad; Rosdiana; Teuku Multazam (Proceedings of International Conference on Multidisciplinary Engineering (ICOMDEN), 2024)
The On Load Tap Changer (OLTC) is an electrical device that functions as a tap changer under load, allowing the adjustment of transformer windings without requiring a power shutdown. To maintain a constant output voltage of 20 kV on the secondary side of a transformer, OLTCs are employed in 60 MVA power transformers. Voltage instability in a power generation system leads to increased OLTC operations. This study aims to analyze the optimization of OLTC tap position settings to enhance voltage stability in a 60 MVA power transformer using the Greedy Algorithm, based on primary voltage, secondary voltage, and OLTC tap position. The research was conducted over the course of one week, from June 1 to June 7, 2024. The results show that, when using the Greedy Algorithm, Transformer 1 required only 8 tap position changes, compared to 11 changes with manual calculations and actual data. Similarly, Transformer 2 experienced 7 tap changes, while manual calculations and actual data recorded 10 changes. These findings indicate that, by using the Greedy Algorithm, the transformer taps operate less frequently, which is beneficial for the longevity of the transformer taps. This study concludes that the Greedy Algorithm is effective as an optimization method for OLTC tap settings to maintain voltage stability in 60 MVA transformers.